Perbedaan Hasil Belajar Siswa Melalui Metode Pembelajaran Number Head Together Dan Pembelajaran Konvensional Pada Mata Pelajaran Ekonomi Siswa Kelas Xi MAN 3 Kota Padang - Sri Harti Wahyuni; Citra Ramayani; Mona Amelia (Horizon, 2022)
This study aims to analyze the differences in student learning outcomes through the Number Head Together learning method and conventional learning in the subject of Economics for Class XI MAN 3 Students in Padang City. Based on the analysis of data it is known that both classes of samples are normally distributed and homogeneous. The results of the hypothesis test through One Way Anova obtained the probability value is 0.026 greater than α (0.05) so it can be seen that the probability is smaller than the α which is 0.026 < 0.05. This means that the hypothesis tested (Ha) is accepted at a real level of 5% so that the decision is that H0 is rejected and Ha is accepted so that it can be concluded that there are differences in student learning outcomes through the Number Head Together learning method and conventional learning in the subject of Economics Class XI MAN 3 Padang City Students. From the results of this study, it is hoped that teachers will apply the Number Head together learning method for theoretical material. This Number Head together learning method can improve student learning outcomes so that problems that occur in the learning process can be overcome.Keyword : Differences, Number Head Together, Learning Method